Communication of the South Korean women's archery team at the 2020 Tokyo olympics - Putranto, Teguh Dwi (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2024)
The victory of each athlete in achieving peak performance in the midst of competition depends on the communication skills of players and coaches. When competing in a competition, communication is very important and cannot be ignored. Whether in individual or group numbers in the middle of the competition, communication becomes even closer. The purpose of this research is to see how athletes and coaches of the South Korean archery women's team communicate during the 2020 Tokyo Olympics finals. This research method is using semiotics (Peirce), the performance of the South Korean women's archery team in the final of the women's team competition is examined. The conclusion of this study shows that communication between archers and coaches is dominated by non-verbal communication in the women's team symbolised by high-fives.